Ethylene Modulates Sphingolipid Synthesis in Arabidopsis - Wu, Jian-xin; Wu, Jia-li; Yin, Jian; Zheng, Ping; Yao, Nan (Frontiers in Plant Science, 2015)
Sphingolipids have essential structural and bioactive functions in membranes and in signaling. However, how plants regulate sphingolipid biosynthesis in the response to stress remains unclear. Here, we reveal that the plant hormone ethylene can modulate sphingolipid synthesis. The fungal toxin Fumonisin B1 (FB1) inhibits the activity of ceramide synthases, perturbing sphingolipid homeostasis and thus inducing cell death. We used FB1 to test the role of ethylene signaling in sphingolipid synthesis in Arabidopsis thaliana. The etr1-1 and ein2 mutants, which have disrupted ethylene signaling, exhibited hypersensitivity to FB1; by contrast, the eto1-1 and ctr1-1 mutants, which have enhanced ethylene signaling, exhibited increased tolerance to FB1. Gene expression analysis showed that during FB1 treatment, transcripts of genes involved in de novo sphingolipid biosynthesis were down-regulated in ctr1-1 mutants but up-regulated in ein2 mutants. Strikingly, under normal conditions, ctr1-1 mutants contained less ceramides and hydroxyceramides, compared with wild type. After FB1 treatment, ctr1-1 and ein2 mutants showed a significant improvement in sphingolipid contents, except the ctr1-1 mutants showed little change in hydroxyceramide levels. Treatment of wild-type seedlings with the ethylene precursor 1-aminocyclopropane carboxylic acid (ACC) down-regulated genes involved in the sphingolipid de novo biosynthesis pathway, thus reducing sphingolipid contents and partially rescuing FB1-induced cell death. Taking these results together, we propose that ethylene modulates sphingolipids by regulating the expression of genes related to the de novo biosynthesis of sphingolipids.